The reasons for underdevelopment: The case of decolonisation in somaliland - Strangio, Donatella (Contributions to Economics, 2012)
The history of Italian colonial affairs has recently attracted renewed interest from historians and economists. It is a complex and involved question. Over the last few years, though perhaps slightly later than the more mature historiography of other European countries, the work of some important scholars has opened up new fields of investigation and research. Recent studies have tried to analyse in greater depth the working mechanisms of the colonial system, broadening the field of investigation also to the perspective of African countries and the political-economic equilibriums of the second half of the 20th century. This study fits into this area of research and analyses crucial aspects of the decolonisation of Somalia, the history of the presence of Italian banking in Somaliland; relations between Italian and Somali institutions; Italian political-monetary policies during the reconstruction and the first economic boom.